Shock advertising – a sensationalised media construct? - Pflaumbaum, Christine G (Curtin University, 2013)
How does the practice of advertising work in comparison to the theory? By presenting the advertisers point of view, this allowed comparability with general rules of shock advertising and its redefinition. The main focus is on the definition of shock advertising, changes of the consumer perception and effectiveness of the system of self-regulation. This study adds to the understanding of shock advertising in a global context, whilst recognising shifts and discrepancies between theory and practice of advertising.